2010
DOI: 10.1038/hr.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitors in cardiac surgery: current studies and controversies

Abstract: Major complications associated with cardiac surgery are still common and carry great prognostic significance. Current medical interventions to prevent these cardiovascular complications include antiplatelet therapy, statins, b-blockers and angiotensinconverting enzyme (ACE) inhibitors. Both experimental studies and clinical trials have shown that ACE inhibitors hold promise as cardiovascular protective agents for cardiac surgery patients. Several lines of evidence support this hypothesis. First, long-term use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Careful attention to the issue of eventual reinstitution of medications for chronic conditions, such as an ACE‐I, is indicated to avoid unnecessary mortality. Because early experience showed that dose titration was a key for successful application of an ACE‐I, practitioners may also need to consider dose modification rather than simply continuation or not restarting . Future research is needed to confirm our results in other healthcare systems and to define mechanisms that link postoperative nonresumption of an ACE‐I to mortality.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Careful attention to the issue of eventual reinstitution of medications for chronic conditions, such as an ACE‐I, is indicated to avoid unnecessary mortality. Because early experience showed that dose titration was a key for successful application of an ACE‐I, practitioners may also need to consider dose modification rather than simply continuation or not restarting . Future research is needed to confirm our results in other healthcare systems and to define mechanisms that link postoperative nonresumption of an ACE‐I to mortality.…”
Section: Discussionmentioning
confidence: 86%
“…tinuation or not restarting 40. Future research is needed to confirm our results in other healthcare systems and to define mechanisms that link postoperative nonresumption of an ACE-I to mortality.…”
mentioning
confidence: 75%
“…The propensity score (x-axis) for PreRASi is the probability given baseline variables that any patient in either group would be selected for PreRASi activity of the sympathetic nervous system as well as the trophic effects of angiotensin II. Thus, RASi, by influencing extracellular matrix content, cellular apoptosis, tissue inflammation, and fibrosis, could hypothetically reverse the left ventricularremodeling process, attenuate aortic valve thickening and prevent thrombosis and plaque rapture 6,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have been reported that consumption of ACEIs and ARAs, until the day of surgery caused hypotension during anesthesia induction (2-4). This point is very important in patients who are a candidate for open-heart surgery with cardiopulmonary bypass (5). It is important to consider that some premedication drugs like benzodiazepines (midazolam), opioids (remifentanil), and anti-convulsion agents (gabapentin and pregabalin) can cause hemodynamic changes during anesthesia induction (6, 7).…”
Section: Introductionmentioning
confidence: 99%